2009
DOI: 10.1097/ypg.0b013e32832080e1
|View full text |Cite
|
Sign up to set email alerts
|

Further evidence for DYX1C1 as a susceptibility factor for dyslexia

Abstract: As significant association was proved in our sample, we could also conclude that denser maps, sex information, and well-defined subphenotypes are crucial to correctly determine the contribution of DYX1C1 to dyslexia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 23 publications
5
57
0
2
Order By: Relevance
“…The results did not support association for the two SNPs reported as associated with dyslexia in Finnish readers. 1 These findings are consistent both with other data, suggesting that the association of markers rs3743205 and rs61761345 identified by Taipale et al may be specific to the Finnish genetic background 4 and with other data suggesting that DYX1C1 is nevertheless associated with reading disability in non-Finnish populations, 28,31 as well as with short-term memory. 28,30 Overall, these data significantly increase support for a role of DYX1C1 in dyslexia and, perhaps separately, in short-term storage of verbal information.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The results did not support association for the two SNPs reported as associated with dyslexia in Finnish readers. 1 These findings are consistent both with other data, suggesting that the association of markers rs3743205 and rs61761345 identified by Taipale et al may be specific to the Finnish genetic background 4 and with other data suggesting that DYX1C1 is nevertheless associated with reading disability in non-Finnish populations, 28,31 as well as with short-term memory. 28,30 Overall, these data significantly increase support for a role of DYX1C1 in dyslexia and, perhaps separately, in short-term storage of verbal information.…”
Section: Discussionsupporting
confidence: 81%
“…1 These findings are consistent both with other data, suggesting that the association of markers rs3743205 and rs61761345 identified by Taipale et al may be specific to the Finnish genetic background 4 and with other data suggesting that DYX1C1 is nevertheless associated with reading disability in non-Finnish populations, 28,31 as well as with short-term memory. 28,30 Overall, these data significantly increase support for a role of DYX1C1 in dyslexia and, perhaps separately, in short-term storage of verbal information. 30 These data suggest a new candidate for a functional mutation in DYX1C1; given the known role of DYX1C1 in neuronal migration, 17,18 the results bolster the early observation of Galaburda et al 55 that dyslexia may be associated with molecular layer ectopia and microgyria.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The markers rs600753 and rs16787 were previously found to be significant in several combinations of haplotypes [Dahdouh et al, 2009]. The rs1789126 marker was selected because of a positive association in an Australian sample [Bates et al, 2010], and the rs1289331 was selected as it was suggested to be the binding site of the SP1 transcription factor [Tapia-Paez et al, 2008].…”
Section: Family-based Association Analysismentioning
confidence: 99%
“…DYX1C1 has also been associated with reading and spelling ability in a large unselected group of adolescents from Australia. 15 Furthermore, it has been shown that dyslexia-associated variants within the promoter region of DYX1C1 16 influence the binding affinity of transcription factor complexes. 17 Two genes have been reported to be associated with dyslexia within the linkage region on chromosome 6p22.2: DCDC2 (doublecortin domain-containing protein 2, MIM 605755) [18][19][20] and KIAA0319 (MIM 609269).…”
Section: Introductionmentioning
confidence: 99%